Using Changes in Auction Maturity Sectors to Help Identify the Impact of QE on Gilt Yields. (May 2014) - McLaren, Nick; Banerjee, Ryan N.; Latto, David
<x xml:space="preserve">Abstract</x> This article uses a novel way of identifying part of the impact of quantitative easing (QE) on gilt yields, using natural experiments associated with Bank of England announcements about changes in the maturity distribution of future gilt purchases. We find that changes in expected QE purchases had a significant effect on gilt yields following each announcement in March 2009, August 2009 and February 2012. The local supply effects we identify appear to be important: they may account for around half of the total impact on gilt yields in these events, and are passed through to yields of related assets.